KONTRIBUSI EKSTRAKURIKULER BOLABASKET TERHADAP PEMBIBITAN ATLET DAN PENINGKATAN KESEGARAN JASMANI - Tri Ani Hastuti (Jurnal Pendidikan Jasmani Indonesia, 2010)
Abstract The idea that physical education is to improve physical fitness is impossible because the limited time provided in secondary high school curriculum. Therefore, the policy to have sports as extracurricular is important which are driven to provide programs based on students interest, talents, situation, and needs. Basketball as an extracurricular contributes to improve students physical fitness and also talent scouting. Regular and systematic exercise will improve physical fitness components such as : (1) cardiorespiratory endurance, (2) muscle strength and endurance, (3) flexibility, (4) body composition. Basketball as an extra curricular program functions as development of basketball elite athletes. Kata kunci : ekstrakurikuler bolabasket, pembibitan, kesegaran jasmani.